Rickets, Growth, and Alkaline Phosphatase in Urban Adolescents. Issue 5914 (11th May 1974) - Cooke, W. T.; Asquith, P.; Ruck, Nicola; Melikian, V.; Swan, C. H. J.
Abstract : Calciferol therapy for 12 months in white, Asian, and West Indian schoolchildren resulted in a highly significant increase in height and weight when compared with schoolchildren not so treated. The rate of fall of serum alkaline phosphatase was similar in both the treated and untreated schoolchildren and in other children treated in hospital for rickets. Dietary studies on 9% of the total survey by weighed inventory methods showed a low average intake of vitamin D, while random estimates of 25-hydroxycalciferol levels on 6% of the children were less than 3·8 ng/ml in 40% of those studied (principally Asian). It was concluded that there was a significant problem of vitamin D deficiency among Asian and West Indian teenagers and that white children were also affected to a less degree.